Patriarchy, Religion and Women’s Subjugation in Adichie’s Purple Hibiscus - Singh, Raj Kishor (SCHOLARS: Journal of Arts & Humanities, 2024)
This paper explores the intricate portrayal and symbolic nuances of patriarchy and religion as fervent sources of intolerance within Chimamanda Ngozi Adichie's Purple Hibiscus (2003). The study transcends the binary view of these forces, scrutinizing their dynamic interplay and discerning their nuanced expressions within the depicted characters and broader societal constructs. The examination traverses beyond the surface-level manifestations, rummaging into the intricate fabric of power dynamics, gender roles and cultural norms to unravel their profound impact on individual conduct and the structural foundations of society. Drawing on theoretical frameworks, this study invokes John Locke's Two Treatises of Government and A Letter Concerning Toleration (2003) and Michel Foucault's Discipline and Punish (1995) to dissect patriarchy and religious practices as intricate manifestations of intolerance. By situating the analysis within these theoretical underpinnings, the study unveils the multifaceted layers of control, discipline and ideological enforcement inherent in these forces. The culmination of this exploration propels beyond a mere diagnosis of the issues at hand. It advocates for a transformative shift, contending that the perpetuation of patriarchy and religious fanaticism must be dismantled for the collective well-being of families and society at large. This call for cessation transcends mere condemnation, urging a profound reevaluation of ingrained societal structures and norms. Beyond its contribution to literary discourse, this study seeks to offer a deeper comprehension of the pervasive influence of intolerance, shedding light on its contemporary relevance. By pushing the boundaries of traditional analyses, this paper aspires to be a catalyst for transformative discussions on the dismantling of oppressive forces, paving the way for a more enlightened and inclusive future.